1985
DOI: 10.1038/clpt.1985.89
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine: Influence of renal function on pharmacokinetic/hemodynamic relationship

Abstract: The hemodynamic effects and kinetics of nifedipine were examined in four groups of five subjects with different degrees of impaired renal function. In a randomized order, each subject received nifedipine by an intravenous infusion (4.5 mg in 45 minutes) and by mouth as a sustained-release tablet (20 mg). Plasma concentrations of nifedipine and urinary metabolite excretion were measured by liquid chromatography. Heart rate, blood pressure, forearm blood flow, and plasma norepinephrine levels were examined seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 4 publications
4
20
1
Order By: Relevance
“…However, we found no difference in the binding of the parent drugs measured after single dosing, during chronic treatment, and in vitro (Table 1). The extent of nifedipine binding measured in our study (Table 1) was within the limits reported previously in plasma in vitro: 0.8-4% unbound (Von Rosenkrantz et al, 1974;Otto & Lesko, 1986;Kleinbloesem et al, 1985).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, we found no difference in the binding of the parent drugs measured after single dosing, during chronic treatment, and in vitro (Table 1). The extent of nifedipine binding measured in our study (Table 1) was within the limits reported previously in plasma in vitro: 0.8-4% unbound (Von Rosenkrantz et al, 1974;Otto & Lesko, 1986;Kleinbloesem et al, 1985).…”
Section: Discussionsupporting
confidence: 66%
“…Because of this, more reliable binding data may be obtained using the serum of patients under drug treatment. Comparing such ex vivo data with those found in vitro may detect the influence of metabolites (known and unidentified) and other possible factors which are absent under in vitro conditions There are data on the plasma binding of nifedipine (Von Rosenkrantz et al, 1974;Kleinbloesem et al, 1985;Otto & Lesko, 1986) and verapamil (Schomerus et al, 1976;Yong et al, 1980;Keefe et al, 1981;McGowan et al, 1983) in vitro and after intravenous administration (McGowan et al, 1983;Kleinbloesem et al, 1985). The concentration of metabolites is low after intravenous dosing (Waller et al, 1984) and might not influence the binding of unchanged nifedipine.…”
Section: Introductionmentioning
confidence: 99%
“…Gradual administration by slow-release tablet, by a rectal osmotic preparation and by slow i.v. infusion without bolus blunts the early tachycardia although the hypotensive effect still occurs (Kleinbloesem et al, 1984c(Kleinbloesem et al, , 1985. Our data suggest that cardiovascular adaptation is rapid.…”
Section: Discussionmentioning
confidence: 57%
“…The protein binding of two dihydropyridine derivatives nifedipine and nitrendipine (Ankermann et al, 1989;Kleinbloesem et al, 1985) was found to be reduced in patients with renal impairment resulting in a significant increase in volume of distribution. The protein binding in the present study was about 98% for the three groups and the volume of distribution was not different between groups 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Several pharmacologically inactive metabolites are produced 60% of which are excreted via bile and 40% excreted via urine, with less than 1% of the parent drug being eliminated unchanged by the kidney. In general, the metabolism of highly extracted drugs is considered only to be significantly affected by disease of the liver, and not by renal impairment, and many investigators have reported that the pharmacokinetics of calcium antagonist drugs such as verapamil (Mooy et al, 1985) or nifedipine (Kleinbloesem et al, 1985) are not affected by renal impairment. However, since cardiovascular disease and renal impairment frequently coincide, it is important to consider and document the clinical pharmacology of calcium antagonist drugs in patients with renal impairment.…”
Section: Introductionmentioning
confidence: 99%